1997
DOI: 10.1038/sj.sc.3100364
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle fibre type transformation following spinal cord injury

Abstract: Following spinal cord injury (SCI), upper motor neuron paralysed muscles lose the normal type I (slow) and II (fast) ®bre mosaic pattern and become predominantly composed of type II (fast glycolytic) ®bres). The majority of the research demonstrating this ®bre type shift was based on pH sensitive myo®brillar ATPase staining techniques on muscle from longstanding paraplegics and quadriplegics. The purpose of this study was to describe muscle ®bre type changes over a wide time spectrum post SCI using immuno¯uore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
173
3
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(199 citation statements)
references
References 18 publications
18
173
3
5
Order By: Relevance
“…RTD is dependent on myosin ATPase activity and is directly related to the proportion of type IIb fibres. 12 Previous studies have shown that muscles undergo a fibre-type transformation towards a greater representation of type IIb fibres in vastus lateralis 1,13,14 and soleus muscles 2 after SCI. There is some suggestion that the degree of fibre-type transformation may be influenced by the amount of spasticity in a particular muscle after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…RTD is dependent on myosin ATPase activity and is directly related to the proportion of type IIb fibres. 12 Previous studies have shown that muscles undergo a fibre-type transformation towards a greater representation of type IIb fibres in vastus lateralis 1,13,14 and soleus muscles 2 after SCI. There is some suggestion that the degree of fibre-type transformation may be influenced by the amount of spasticity in a particular muscle after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…6 Following SCI, it is well documented in humans [28][29][30][31] and animals 24,32,33 that skeletal muscles below the level of an upper motor neuron lesion undergo marked changes in their morphological, metabolic, and contractile properties. 34 Changes in spastic skeletal muscle generally include atrophy, loss of elasticity and relative increase in the connective tissue within the muscles, ingravescent accumulation of lipid, interstitial fibrosis and microcirculatory alteration. 7,24,29,34 Spastic muscles develop involuntary tetanic contraction, which produced a marked loss of sarcomeres in this muscles, which was greater than that from immobilization alone.…”
Section: Discussionmentioning
confidence: 99%
“…34 Changes in spastic skeletal muscle generally include atrophy, loss of elasticity and relative increase in the connective tissue within the muscles, ingravescent accumulation of lipid, interstitial fibrosis and microcirculatory alteration. 7,24,29,34 Spastic muscles develop involuntary tetanic contraction, which produced a marked loss of sarcomeres in this muscles, which was greater than that from immobilization alone. 7,35 In SCI patients, slow-to-fast conversion that is the major effect of a spinal cord transection 36 occurred in early stages (o4 weeks) postinjury, and reached gradually the new steady state characterized by a predominance of fibers expressing only the fast by 73 months.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in average muscle cross-sectional area (CSA) [8], replacement of Type I muscle fibers by Type II fibers [4], infiltration of adipose tissue inside muscles, reduction in the oxidative enzyme level, mitochondria concentration, and number of capillaries are observed in muscles located below the injury level [3,18,21].…”
Section: Introductionmentioning
confidence: 99%